2002
DOI: 10.1021/bi026546a
|View full text |Cite
|
Sign up to set email alerts
|

Two Tarantula Peptides Inhibit Activation of Multiple Sodium Channels

Abstract: Two peptides, ProTx-I and ProTx-II, from the venom of the tarantula Thrixopelma pruriens, have been isolated and characterized. These peptides were purified on the basis of their ability to reversibly inhibit the tetrodotoxin-resistant Na channel, Na(V) 1.8, and are shown to belong to the inhibitory cystine knot (ICK) family of peptide toxins interacting with voltage-gated ion channels. The family has several hallmarks: cystine bridge connectivity, mechanism of channel inhibition, and promiscuity across channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
207
5
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(229 citation statements)
references
References 47 publications
15
207
5
2
Order By: Relevance
“…This library could be engineered from the terrific variety of potent, VGIC subtype-selective VSTs that are increasingly being discovered. Examples of VSTs from spiders include ω-Agatoxin-IVA, which binds P-type Ca 2+ channels (58) and the ProTx-I and -II peptides, which bind Na + channel subtypes (59)(60)(61)(62), and heteropodatoxins, which bind Kv4 channels (63). The library of known VSTs is growing rapidly as venom peptides and mRNAs of more predatory animals are sequenced (64).…”
Section: Discussionmentioning
confidence: 99%
“…This library could be engineered from the terrific variety of potent, VGIC subtype-selective VSTs that are increasingly being discovered. Examples of VSTs from spiders include ω-Agatoxin-IVA, which binds P-type Ca 2+ channels (58) and the ProTx-I and -II peptides, which bind Na + channel subtypes (59)(60)(61)(62), and heteropodatoxins, which bind Kv4 channels (63). The library of known VSTs is growing rapidly as venom peptides and mRNAs of more predatory animals are sequenced (64).…”
Section: Discussionmentioning
confidence: 99%
“…Although these toxins may trap the IV-S4 in the closed configuration, they impair inactivation and are excitatory. ProTx-II, from the venom of the tarantula Thrixopelma pruriens, has been shown to inhibit sodium currents, but in contrast to HWTX-IV, ProTx-II obviously modifies the voltage dependence of VGSC activation in the physiological voltage range (22). It also had been proposed that ProTx-II might interact with neurotoxin receptor site 4 (52).…”
Section: Discussionmentioning
confidence: 99%
“…Many toxins from spiders, such as ␦-atracotoxins; Magi5; CcoTx1, CcoTx2, and CcoTx3; PaurTx3; and ProTx-II, are able to shift the threshold of sodium channel activation to more negative or positive potentials (21)(22)(23)(24)(25)(26). Therefore we investigated the effects of subsaturating toxin concentrations on the voltage dependence of current activation.…”
Section: Effects Of Subsaturating Concentrations Of Hwtx-iv On Activamentioning
confidence: 99%
“…The only sequence conservation between these peptides and MrVIA/MrVIB is the high content of cysteine residues, with the ProTx peptides containing six cysteine residues and kurtoxin containing eight. The disulfide connectivity has been elucidated for the ProTx peptides and shown to be Cys I -Cys IV , Cys II -Cys V , and Cys III -Cys VI (48). It has been suggested that they contain an inhibitor cystine knot motif based on this connectivity.…”
Section: Fig 11 Depolarization-activated Camentioning
confidence: 99%